Frames of war : when is life grievable? - Butler, Judith. 1956- (London : New York : Verso, 2010)
"Frames of War begins where Butler's Precarious Lives left off: on the idea that we cannot grieve for those lost lives that we never saw as lives to begin with. In this age of CNN-mediated war, the lives of those wretched populations of the earth -- the refugees; the victims of unjust imprisonment and torture; the immigrants virtually enslaved by their starvation and legal disenfranchisement -- are always presented to us as already irretrievable and thereby already lost. We may shake our heads at their wretchedness but then we sacrifice them nonetheless, for they are already forgone. By analyzing the different frames through which we experience war, Butler calls for a reorientation of the Left toward the precarity of those lives. Only by recognizing those lives as precarious lives -- lives that are not yet lost but are ever fragile and in need of protection -- might the Left stand in unity against the violence perpetrated through arbitrary state power. -- Publisher description.
Introduction: Precarious Life, Grievable Life --- 1. Survivability, Vulnerability, Affect --- 2. Torture and the Ethics of Photography: Thinking with Sontag --- 3. Sexual Politics, Torture, and Secular Time --- 4. Non-Thinking in the Name of the Normative --- 5. The Claim of Non-Violence.
Originally published: 2009.
Includes bibliographical references and index.
Keywords: Violence -- Social aspects; Violence -- Political aspects; Political violence; Mass media and public opinion -- United States; Right and left (Political science); Violence -- Social aspects; Violence -- Political aspects; Political violence; Mass media and public opinion -- United States; Right and left (Political science); Kriegsverbrechen; Folter; Gewaltmonopol; Gewaltkriminalität.; USA